The legal environment of revitalization ventures of urban areas and the proceeding of public administration - Biliński, Tadeusz; Kucharczyk, Emilia (Budownictwo i Architektura / Civil and Architectural Engineering, 2018)
The paper presents in general characterization of revitalization ventures of urban areas, special attention paying to their complexity and importance to the sustainable socio-economic development of the whole agglomeration. The fundamental value of this study is a comprehensive and consistent presentation of legal conditions in the entire spatial reorganization process of urban built-up areas. Presentation of individual, consecutive, normative acts and local law documents together with commentary allows a full, multi-faceted view of the construction of spatial order in the process of urban revitalization. The assignment of the following to each of the following activities related to the implementation of revitalization projects, relevant legal provisions, facilitates programming, planning, designing, and fi nally the implementation of comprehensive revitalization projects of urban areas. In this proceeding the role of public administration, both local government and governmental, was distinguished.